Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/dev.21952
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal hair cortisol concentrations are related to maternal prenatal emotion dysregulation but not neurodevelopmental or birth outcomes

Abstract: Hair cortisol concentrations measured during pregnancy have emerged as a novel biomarker for prenatal stress exposure. However, associations between prenatal stress and distress, broadly defined, and hair cortisol concentrations during pregnancy are inconsistent. We examined relations among hair cortisol concentrations during the third trimester with (a) emotion dysregulation and (b) detailed measures of maternal prenatal stress. We also examined the predictive validity of maternal hair cortisol during pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…The findings of the current study do not support those of studies reporting positive associations between hair cortisol concentrations and psychological stress during pregnancy ( Kalra et al, 2007 , Hoffman et al, 2016 ), or between hair cortisol concentrations and emotion dysregulation during pregnancy ( Conradt et al, 2020 ). However, our results are in line with those of multiple other studies that do not find associations between hair cortisol and psychological stress during pregnancy ( Kramer et al, 2009 , Galbally et al, 2019 , Orta et al, 2019 , Conradt et al, 2020 ). In general, these studies, as well as our current study, used psychological stress measures that reflected daily, short-term disturbances in stress, while hair cortisol is thought to reflect more chronic cortisol secretion ( Mustonen et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current study do not support those of studies reporting positive associations between hair cortisol concentrations and psychological stress during pregnancy ( Kalra et al, 2007 , Hoffman et al, 2016 ), or between hair cortisol concentrations and emotion dysregulation during pregnancy ( Conradt et al, 2020 ). However, our results are in line with those of multiple other studies that do not find associations between hair cortisol and psychological stress during pregnancy ( Kramer et al, 2009 , Galbally et al, 2019 , Orta et al, 2019 , Conradt et al, 2020 ). In general, these studies, as well as our current study, used psychological stress measures that reflected daily, short-term disturbances in stress, while hair cortisol is thought to reflect more chronic cortisol secretion ( Mustonen et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Yet, results for hair cortisol are mixed as well ( Mustonen et al, 2018 ). Some studies have shown that hair cortisol is positively linked to prenatal psychological stress ( Kalra et al, 2007 , Hoffman et al, 2016 ) and to maternal emotion dysregulation (albeit not to episodic and chronic stress; Conradt et al, 2020 ), yet others did not replicate these findings ( Kramer et al, 2009 , Galbally et al, 2019 , Orta et al, 2019 ). To date, only one study investigated the associations between maternal prenatal cortisol, when measured in hair, and infant temperament ( Enlow et al, 2017 ), revealing that maternal prenatal hair cortisol was negatively correlated with infant rate of recovery from distress.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is accumulating for the role of ER during pregnancy in the physical and mental health of pregnant people. Poor ER has been associated with increased hair cortisol in pregnant women (Conradt et al 2020 ), as well as with smoking and other substance use (Bradizza et al 2017 ), eating behaviors and obesity (de Campora et al 2014 ), and sleep problems (Kalmbach et al 2020 ) during pregnancy. For individuals experiencing pregnancy-related anxiety (Basharpoor and Taherifard, 2019 ), high levels of stress (Lin et al 2019 ), or worries due to medical complications during pregnancy (McCoyd et al 2020 ), ER is also implicated, in that challenges effectively regulating these emotional states during pregnancy may result in their maintenance or exacerbation.…”
Section: Health and Mental Health Of The Pregnant Personmentioning
confidence: 99%
“…17 Studies evaluating the effects of stress and psychopathology on maternal and foetal HCC during pregnancy and beyond are rapidly emerging, but results are inconclusive. [32][33][34][35][36][37][38] This might be partly explained by differences in study sample (i.e. healthy versus depressed mothers) and different definitions of 'stress' (i.e.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%